2015
DOI: 10.1118/1.4908223
|View full text |Cite
|
Sign up to set email alerts
|

Investigating CT to CBCT image registration for head and neck proton therapy as a tool for daily dose recalculation

Abstract: In this work, the authors generated CBCT based stopping power distributions using DIR of the pCT to a CBCT scan. DIR accuracy was below 1.4 mm as evaluated by the SIFT algorithm. Dose distributions calculated on the vCT agreed well to those calculated on the rpCT when using gamma index evaluation as well as DVH statistics based on the same contours. The use of DIR generated contours introduced variability in DVH statistics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
146
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(155 citation statements)
references
References 43 publications
4
146
1
Order By: Relevance
“…6. These results were slightly better than the 2.8±0.2 mm, 1.0±2.0 mm, and 1.0±0.2 mm errors observed in similar studies that employed different DIR algorithms 7 , 24 , 25 , 26 …”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…6. These results were slightly better than the 2.8±0.2 mm, 1.0±2.0 mm, and 1.0±0.2 mm errors observed in similar studies that employed different DIR algorithms 7 , 24 , 25 , 26 …”
Section: Resultscontrasting
confidence: 51%
“…Advanced analysis tools to evaluate the distal range of the proton beam, polar WET maps, tracking PDR changes as well as the potential to compute the “dose of the day” 7 , 26 using the cCBCT, are some applications that may be developed using volumetric imaging to leverage the maximum benefit from the unique properties of proton dose distribution. If this analysis can be automated, it may be possible to use CBCT to trigger further action such as dose calculation on the cCBCT or resimulation and replanning.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 However, we believe it necessary for this to be independently conducted since the residual HU errors after the scatter correction would have different effects on proton dose calculations compared to photon cases. Moreover, this validation cannot be done in real patient images, as there would be no ground truth of CT ref to compare with daily CBCT images unless CT and CBCT images are acquired at the same patient setup as pointed out by Landry et al 12 Recently, Landry et al 12,13 investigated the feasibility of proton dose calculations on a virtual CT image using deformable image registration between plan CT and daily CBCT images. Even though they demonstrated a promising WEPL error (2% error of the proton range), they encountered residual DIR errors of 2-3 mm which potentially degrade the effectiveness T III.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been few studies on CBCT imaging for APT. 12,13 It is expected that the HU accuracy of CBCT is more crucial in APT than it is in ART, because small HU differences may cause range errors and absolute dose errors, which will in turn lead to reduced integrity of the dose calculation. 14 To date, no study has demonstrated proton dose calculation or treatment planning on either raw or scatter-corrected CBCT images.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al investigated that dose calculation based on modified CBCT (mCBCT) was more accurate than directly on the basis of CBCT 18. Landry et al reported that dose distributions calculated on the modified CBCT agreed well to those calculated on the CT when using gamma index evaluation, as well as DVH statistics based on the same contours 19. This means that mCBCT has potential to account for interfractional dosimetric uncertainness.…”
Section: Introductionmentioning
confidence: 99%